Formation of calcium chloride brines in volcaniclastic-rich sediments - Sena, Clara; Parkhurst, David L.; Tepley |||, Frank J.; Jiang, Fuqing; van der Land, Cees; Coelho, Francisco JRC; Oliveira, Vanessa; Lever, Mark A.; Ishizuka, Osamu; Arculus, Richard (Frontiers in Earth Science, 2022)
The Amami-Sankaku Basin, located in the Philippine Sea, records approximately 50 million years of sediment accumulation and diagenesis of volcanic ash derived from the Kyushu-Palau and Kyushu-Ryukyu arcs. Analyses of porewater and sediment samples from the 1461-m core recovered at IODP Expedition 351, Site U1438, included major and trace elements, strontium radiogenic isotope ratio (87Sr/86Sr), and taxonomic identification of archaeal classes and bacterial orders. Sediment X-ray diffraction and thin section analyses show that smectite, zeolites and chlorite are the main authigenic minerals. A multicomponent solute diffusion and reaction numerical model was developed to simulate the long-term diagenesis that took place in this sedimentary sequence and to account for the transition to a calcium chloride brine at about 670 mbsf. Numerical results indicate that 45% of the initial amount of volcanic ash has been dissolved at 750 mbsf. At this depth, 13% of the initial water (H2O) in the pore space is estimated to have been transferred to the solid phase by the formation of zeolites, which accounts for an increase in porewater chloride concentration. In contrast, dissolution of anorthite and volcanic ash combined with sodium uptake by zeolites accounts for the predominance of calcium in the brine. In the upper 160 m of the sedimentary column, the electrochemical migration of solutes causes chloride to move in the opposite direction of the concentration gradient, i.e., uphill diffusion, sustaining downward diffusion of seawater chloride into the sediments.